Effectiveness of different high temperatures to control stored-product beetles (different species) on stored rice grain / Normazura Ismail and Nur'Amira Hamid - Ismail, Normazura; Hamid, Nur’Amira (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
Heat treatment is being chosen to be an alternative to replace the use of methyl bromide. It involved raising and maintaining the temperature in the warehouse or storage of grain between 50°C to 60°C to control the stored product beetles. The duration may vary from 6 hours to 24 hours based on the types of storage, grains and its quantity. The need for alternatives is vital, considering the statutory limit (until the year 2015) for methyl bromide usage other than for phytosanitary purpose, and the likely widespread occurrence of insect resistance to both methyl bromide and phosphine. To note, these have been used in Malaysia for over half a century. Thus, the objective of this study focusses on testing the effectiveness of lethal temperature and duration in controlling the stored product beetles. High temperatures were used ( 30°C, 60°C, 70°C and 80°C) to decease the stored product beetles which are Sitophilus oryzae, Tribolium casteneum, and Oryzaephilus surinamensis. By using an oven, milled rice with tested beetles were exposed to the heat treatment. Each day, the heat exposures were given for 15 minutes. The number of dead beetles in 6 days exposure and effect on the eating quality of the cooked rice was observed at the end of the treatment. For Sitophilus oryzae, the duration of exposure requires six days of treatment (15 minutes per day) to kill all 25 adults atr the highest temperature (80°C) while theones with the least resistance; Oryzaephilus surinamensis requires 60 minutes. By using an oven, it is recommended that 60°C to 80°C of temperatures in 15 minutes of exposure be adopted to ensure the effectiveness against all species in heat treatment. The eating quality of cooked rice in terms of the aroma, stickiness, taste, colour and overall acceptability was not affected from the multiple exposure (3 times) to the heat treatment. Findings from this study indicated heat treatment is a potential replacement for insecticides. However, it is recommended to use high temperature in range of 60°C to 80°C in a short time (within 15 minutes) of exposure. Thus, heat treatment can be used for commercial application rice mill producer to control stored product insects during storage phase and milling process.